Inflammation after corneoscleral rupture and traumatic cataract due to blunt trauma in a child: a case report - Clara Verlina Suhardi; Graecia Bungaran; Nashrul Ihsan (Intisari Sains Medis, 2021)
Background: Ocular trauma is the most common cause of acquired monocular blindness in children. It is because of the inflammation following corneoscleral rupture and traumatic cataracts due to blunt trauma. This case study aims to evaluate the corneoscleral rupture and traumatic cataracts due to blunt trauma in a child.Case Presentation: We present a 5-year-old male who sustained blunt trauma to his right eye. He presented with blurry vision, mild pain and watering from the affected eye. His examination revealed visual acuity of 6/60 in the right eye (RE), corneal laceration extending from 3 o’clock towards 11 o’clock with possible extension to the sclera, and cortical lens matter in the anterior chamber. The patient underwent globe rupture repair under general anesthesia immediately. Postoperative day one revealed 2 mm hypopyon thick inflammation cells and fibrin. He was on topical steroids and topical antibiotics. The fourth postoperative day showed reduced inflammation, wound sutures in place and absence of hypopyon, thick membranous in the pupil. The patient is then referred to the Pediatric Ophthalmology department for a follow-up operation of clearing lens particle remnants to reduce inflammation and IOL insertion. Conclusion:  Management of the injury and traumatic cataract is crucial to prevent vision loss and amblyopia, to maintain binocularity, prevent strabismus or even phthisis bulbi. Along with early management, routine follow-up examination for prevention of other unwanted complications is advised.